HUBUNGAN KONSUMSI HARIAN DENGAN TINGKAT KEBUGARAN PADA SISWA KELAS IX DI SMPN 1 NGASEM BOJONEGORO - Sukma Waskita Budi Luhur; Pudjijuniarto; Yuliastrid, Dita; Mokh. Nur Bawono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Daily life requires physical fitness, which is defined as the body's ability to adapt to various types of activities. In this case, exercise is good for your health andquality of life. Internal and external factors are twocategories that can affect a person's physical fitness. Internal factors include age, gender, and geneticfactors, while external factors include diet, physicalactivity level, smoking habits, and nutritional status. The purpose of this study was to investigate how thedaily food consumption of ninth-grade students atSMPN 1 Ngasem Bojonegoro correlates with theirfitness levels. With a sample of 66 students selected atrandom, a quantitative correlational method was used. After being collected for 24 hours, the Nusantara Student Fitness Test (TKPN) was analyzed usingnormality tests and Spearman's rank correlation. The results showed that most students (52 percent) had fitness in the “fair” category, and that 44 percent ofstudents consumed more than necessary every day. The results of the study showed a significant positiverelationship between the two variables, with a correlation coefficient of 0.752 and significance of0.000 (p < 0.05). Therefore, it was found that anincrease in student fitness levels was influenced byadequate daily consumption.